The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.energyfuels.7b03733
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluations of Polymeric Solubility and Thickeners for Supercritical CO2 at High Temperatures for Enhanced Oil Recovery

Abstract: Supercritical carbon dioxide (scCO2) is considered to be an excellent candidate for miscible gas injection (MGI) because it can reduce oil viscosity, induce in situ swelling of the oil, and reduce the IFT of the in situ fluid system. However, the unfavorable mobility associated with scCO2 flooding poses a major challenge due to the large viscosity contrast between the crude oil and scCO2, resulting in viscous fingering. An effective approach to overcome this challenge is to increase the viscosity of scCO2 (scC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 72 publications
10
55
0
Order By: Relevance
“…Branched polymers were used because experiments [5,10,17] and simulations [53,61] have shown them to be more effective in raising the viscosity than linear ones, under similar thermodynamic conditions. The viscosity is obtained as a function of polymer concentration, branch length and flexibility and as a function of angular bonding strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Branched polymers were used because experiments [5,10,17] and simulations [53,61] have shown them to be more effective in raising the viscosity than linear ones, under similar thermodynamic conditions. The viscosity is obtained as a function of polymer concentration, branch length and flexibility and as a function of angular bonding strength.…”
Section: Discussionmentioning
confidence: 99%
“…Supercritical CO2 is particularly promising as a fracturing fluid because of its liquidlike density, however its viscosity is gaslike, which can be two orders of magnitude lower than the viscosity of water [11]. Low viscosity leads to viscous fingering and low oil mobility [2,10], limiting the applications of CO2 as a fracturing fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies, reported that for low/high molecular weight polymers, a concentration of 1.5-7 wt% is required to thicken CO 2 albeit at very high pressure [6]. In recent studies, [16,17] P-1-D has been found to have sufficient solubility in both CO 2 and associated gas (AG) mixtures (at temperatures above 358 K and pressures of 50-55 MPa) to considerably increase gas viscosity. The viscosity enhancement of P-1-D in an AG mixture (25 mol% CO 2 ) and CO 2 was measured in a capillary viscometer at different pressures (50-55 MPa), 377 K, and varying P-1-D concentrations (1.5-9 wt%).…”
Section: Direct Carbon Dioxide Thickeners 21 Polymeric Thickenersmentioning
confidence: 99%
“…In this context, a possible solution to reduce the impact of the CO 2 release is to reuse it as green solvent 3–8 . Within this perspective, nowadays, supercritical carbon dioxide flooding technology in which CO 2 is injected into an oil layer to increase the oil recovery rate has obtained a great deal of attention 9–15 . The first report of CO 2 thickening with polymers dates back to 1985 by Heller et al 16 It is worth mentioning that carbon dioxide can be sealed underground in this technology which will help to achieve the goal of reducing emissions incidentally 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The first report of CO 2 thickening with polymers dates back to 1985 by Heller et al 16 It is worth mentioning that carbon dioxide can be sealed underground in this technology which will help to achieve the goal of reducing emissions incidentally 12 . However, there are some drawbacks in the flooding process, due to the massive difference in viscosity of the supercritical carbon dioxide and the oil, among them the “sticky finger” phenomenon that leads to an edge displacement phase advancing in the form of a dispersed liquid bundle just like a “finger”, which will greatly affect the efficiency of oil displacement 9,10 . This phenomenon could be reduced if the carbon dioxide viscosity would be increased, therefore, efforts on carbon dioxide thickening have been a subject of increasing interest.…”
Section: Introductionmentioning
confidence: 99%